Pengembangan Leaflet Keanekaragaman Kopi Suku Dayak Salako di Kabupaten Sambas - AGUSTINI, AGUSTINI; Sunandar, Ari; Setiadi, Anandita Eka (Universitas Sulawesi Barat, 2024)
The Salako Dayak community is one of the indigenous tribes in West Kalimantan who utilizes the natural landscape of river basins and forests in Kaliau Village, Sajingan Besar District, Sambas Regency. Coffee is an important commodity that has become an inseparable part of the life of the Salako Dayak people. Researchers developed leaflet media to build students' pride, awareness and interest in the cultural heritage of the Salako Dayak tribe. This research the goal is to determine validity and practicality. diversity leaflet media (Dayak Salako coffee). This research uses the 4-D model recommended by Thiagarajan. The development procedures carried out are: (1) Define, (2) Design, (3) Development. The results of this study show that Folio. meia has evolved is very valid in the media aspect (98.52%), material aspect (87.55%) and is categorized as valid in the language aspect (83.33%). The results of students had a good response to large-scale trials of 82.54% and small-scale trials of 82.63%.